PERANCANGAN SISTEM INFORMASI KEBUTUHAN PANEL LISTRIK BERBASIS DESKTOP PADA PT SARANA ENERGI LISTRIKINDO MANUNGGAL - Sumitra, Tata; Iskandar, Dany N.D. (Universitas Dirgantara Marsekal Suryadarma, 2020)
Sales information system is a management information system that produces a variety of information that could be useful to support sales activities in theÂ PT Sarana Energi Listrikindo Manunggal. Goods sale information system is a part of marketing information, which develop particulay to enchance sales activities by collecting, processing and storing sales data so that data can be reevaluted and be provided as useful information. Implementation of goods sale information system is making a computer application which have a power to representation all of information system. Application of goods sale information system is able to manage selling data such asÂ purchasing goods data transaction, selling goods data transaction, product data, distributes data and data of customer by organization, within make full reported, accurate and always actual. The method use object oriented who solving troubel of software depend on object. The result of application of goods sale information system design is very important, due to the importance of computer application in a company. By using this application, all civitas of goods sale and service can be ascended in quality.